Panoramic dental X-ray exposure leads to oxidative stress, inflammation and apoptosis-mediated developmental defects in zebrafish embryos - Karagöz, Atakan; Beler, Merih; Altun, Büşra Dilara; Ünal, İsmail; Cansız, Derya; Gündüz, Hüseyin; Alturfan, Ahmet Ata; Emekli Alturfan, Ebru; Erçalık Yalçınkaya, Şebnem (Elsevier Masson s.r.l., 2023)
Panoramic x-ray units are widely used in dental radiodiagnostics. Patients are exposed to relatively low radiation doses with panoramic imaging, but considering lifetime frequency of exposure, even a small risk can have serious health consequences. Our aim was to assess the effects of panoramic x-rays at two different exposure times on developing zebrafish embryos, focusing on oxidative stress, inflammation, apoptotic pathways, and development. Zebrafish embryos were divided into three groups: control, standard panoramic (SPE, 5.5 s exposure time) and pedodontic panoramic x-ray group (PPE, 4.8 s exposure time). Optically stimulated luminescence dosimeters were used to measure absorbed doses. Mean radiation doses for SPE and PPE were 7.83 mSv and 5.83 mSv respectively. At the end of 96 h post-fertilization, lipid peroxidation (LPO), nitric oxide (NO), reduced glutathione (GSH), glutathione S-transferase and superoxide dismutase were measured in the embryos. Expressions of genes related with inflammation (tnf?, il6, ill15, il21), immunoregulation (ifng) and apoptosis (p53, bax, casp2, casp3, casp8) were determined by RT-PCR. Even at reduced doses at high-speed mode, developmental toxicity was observed in both groups as evidenced by decreased pigmentation, yolk sac oedema, and spinal curvature. While deterioration of oxidant-antioxidant balance, suppression of immune response, induction of inflammation and apoptosis were observed through increased LPO, NO, decreased GSH, ifng, and increased expressions of genes related with inflammation and apoptosis, these effects were more pronounced in the SPE group. These results demonstrate the influence of exposure time and indicate the need for further consideration of optimal panoramic modes from a radiation-induced damage perspective.
Keywords: Apoptosis; Development; Diagnostic X-Rays; Panoramic; Zebrafish Embryos